PENGARUH E-LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Nadila Rezky; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to determine the effect of E-learning on the learning motivation of economic education students at the University of Riau. The population of this study were all active students of economic education at the University of Riau with a total population of 338 students. The sampling technique used was stratified random sampling, which resulted in a sample of 78 students. This research is a quantitative research with a quantitative descriptive approach. The data analysis technique used descriptive analysis and inferential analysis. The results showed that there was a significant and positive effect between E-learning on the learning motivation of students of economic education at the University of Riau, as evidenced by the probability value <0.05 (0.000<0.05), then Ha was accepted. The results showed that E-learning had an effect of 45% on the learning motivation of students of economic education at the University of Riau.Keywords : E-learning, covid-19, Motivation to Learn.